Kewenangan PPAT dalam Pembuatan AJB Terkait Tanah Warisan Milik Anak di Bawah Umur - Yuli Adha Hamzah; Arianty Anggraeny Mangarengi (CV. Social Politic Genius (SIGn), 2022)
This research aims to examine and analyze the authority of PPAT in making AJB related to heritage land owned by a minor and identify the factors that hinder the sale and purchase of heritage land rights. The study used normative and empirical research methods, including direct interviews and a literature review of legal materials. Results showed that the PPAT will conduct a preliminary examination of the documents of the sale and purchase of land rights to avoid problems arising due to failure to meet material and formal requirements. Specifically, the seller must attach the Court Decision on the legal guardian, the testator’s death certificate, and the inheritor’s certificate to fulfill the formal requirement of the legal acts. Furthermore, the factors that hinder the sale and purchase of heritage land rights: are document availability, coordination among related parties, legal and bureaucratic procedures, and personal or psychological factors. Therefore, it is recommended that PPAT, Courts, and other parties involved in the sale and purchase of heritage land rights actively improve communication and coordination. Additionally, it is essential to simplify legal procedures and bureaucracy associated with making AJB, including managing required documents such as the Court Decision on the legal guardian, the testator’s death certificate, and the inheritor’s certificate. Furthermore, legal training and education for PPAT and related parties are needed to increase understanding of the material and formal requirements that must be met in the legal act of the sale and purchase of heritage land rights.